Closing a Window for Massive Photons - Sergio A. Hojman; Benjamin Koch (Advances in High Energy Physics)
Working with the assumption of nonzero photon mass and a trajectory that is described by the nongeodesic world line of a spinning top we find, by deriving new astrophysical bounds, that this assumption is in contradiction with current experimental results. This yields the conclusion that such photons have to be exactly massless.